Water security in Southern Africa: addressing climate change, governance failures, and infrastructure challenges through adaptive solutions - Mokone, Neo (Frontiers in Water, 2025)
Water security is a major challenge in Southern Africa where climate change, weak governance, and aging infrastructure threaten sustainable water access. The paper aims to assess the state of water security in Southern Africa and highlight adaptive strategies for sustainable management. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020), the paper synthesize existing research on water availability, climate change, infrastructure, and governance focusing on Botswana, Mozambique, Namibia, South Africa, Zambia, and Zimbabwe. Findings reveal significant inequalities in water access: rural households face unreliable and unsafe supplies, while urban systems are strained by population growth. Climate-induced droughts and floods intensify scarcity, threatening agriculture, energy, and health. Poor institutional coordination and limited investment further constrain effective water management. Women in rural areas bear unequal water collection burdens, deepening inequities. The paper calls for sound water governance and investment in climate-resilient infrastructure. It also advocates for regional cooperation and gender-inclusive policies to ensure fair and sustainable water access. By consolidating fragmented literature, it contributes actionable insights for policy and resilience planning. Its implications extend to guide policymakers in developing adaptive, fair, and long-term water management strategies in response to growing climate and socio-economic pressures.